Dynamics of Anisotropic Break‐Up in Nanowires of FCC Lattice Structure. Issue 9 (17th July 2019) - Gorshkov, Vyacheslav N.; Sareh, Pooya; Tereshchuk, Vladimir V.; Soleiman‐Fallah, Arash
Abstract: Nanowires are known to be thermally unstable and may break up into chains of nanoparticles at temperatures below their melting point. This phenomenon is reminiscent of the well‐known Rayleigh–Plateau instability of liquid jets, when periodic sausage‐like perturbations of the jet surface increase with time. The corresponding nanowire/jet shape modifications must be followed by a decrease in total surface energy. However, unlike isotropic liquid jet surfaces, the realization of this abatement in the system with a strong lattice structure and physical dissimilarity of bounding facets, leads to specific features of nanowire break‐up, namely, significant variations in the size of nanodrops and the average distance between them, the formation of long‐living dumbbells, and zigzag‐like structures. Here, the physical mechanisms of such diversity are analyzed. Apart from scientific insights, the yielded results can be potentially useful in applications such as the development of optical waveguides based on ordered nanoparticles chains. Abstract : The effects of the nanowire orientation relative to the axes of symmetry of its internal crystal structure on its disintegration into nanoclusters are studied. A qualitative interpretation is given for the variety of quantitative characteristics of the break‐up observed in experiments. The contribution to the classical Plateau–Rayleigh instability of factors that are characteristic only for crystalline "jets" is studied.